2019
DOI: 10.1097/prs.0000000000005536
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Plastic Surgery In-Service Examination Can Predict Success on the American Board of Plastic Surgery Written Examination

Abstract: Background: Originally developed for resident self-assessment, the Plastic Surgery In-Service Examination has been administered for over 45 years. The Accreditation Council for Graduate Medical Education requires that at least 70 percent of graduates pass the American Board of Plastic Surgery Written Examination on their first attempt. This study evaluates the role of In-Service Exam scores in predicting Written Exam success. Methods: In-Service Exam sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…Given that previous studies have demonstrated a direct correlation between performance on the ITE and ABIM certification exam pass rate for first-time takers in internal medicine [8][9][10][11]27], we hypothesized that the AEP, among other factors, would have a downstream favorable impact on ABIM certification amongst exposed residents, as shown by a non-significant trend towards a higher 3-year rolling pass rate for first-time takers. Similar correlations have been observed in other specialties, including emergency medicine [28], surgical specialties [29][30][31][32], and obstetrics and gynecology [33].…”
Section: Discussionsupporting
confidence: 77%
“…Given that previous studies have demonstrated a direct correlation between performance on the ITE and ABIM certification exam pass rate for first-time takers in internal medicine [8][9][10][11]27], we hypothesized that the AEP, among other factors, would have a downstream favorable impact on ABIM certification amongst exposed residents, as shown by a non-significant trend towards a higher 3-year rolling pass rate for first-time takers. Similar correlations have been observed in other specialties, including emergency medicine [28], surgical specialties [29][30][31][32], and obstetrics and gynecology [33].…”
Section: Discussionsupporting
confidence: 77%
“…In line with the historic data on board passage, 11 our CCC recommends a textbook reading plan from any of the various comprehensive plastic surgery textbooks to any resident who scores below the 30th percentile on the In-service Examination. This specific ILP is not meant to be punitive in nature, but more so an acknowledgment that a structured reading program will assist the resident in the intellectual maturation associated with life-long learning and application of acquired skills as a practitioner of the art of surgery, as opposed to the regurgitation of facts for the satisfactory completion of a medical school examination.…”
Section: The Duke Experience: a Case Study In The Benefits Of Forming A CCCmentioning
confidence: 99%
“…Indeed, scores on this examination predict whether a graduate will pass the American Board of Plastic Surgery written examination. 11 Low rates of Board passage can result in an entire program being placed on probation. A plastic surgery program is judged successful by the ACGME if either of the following is true:…”
Section: Responsibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This examination allows residents to assess their knowledge of core plastic surgery topics, gauge their knowledge against national peers, and serve as an indicator of areas needing concentrated educational efforts. Recent work has demonstrated that performance on the PSITE can predict success on the American Board of Plastic Surgery Written Examination, 1 thereby further increasing motivation to prepare for and perform well on this examination. The American Society of Plastic Surgeons’s In-service Examination Committee prepares the questions.…”
Section: Introductionmentioning
confidence: 99%